1992
DOI: 10.1128/mcb.12.7.3060
|View full text |Cite
|
Sign up to set email alerts
|

Genome digestion is a dispensable consequence of physiological cell death mediated by cytotoxic T lymphocytes.

Abstract: We examined virally transformed murine fibroblast clones as targets for cytotoxic T lymphocyte (CTL)-triggered lysis and genome digestion. Strikingly, while all clones were essentially equivalent in the ability to be lysed, one clone, SV3T3-B2.1, failed to exhibit genome digestion associated with CTL attack. Other aspects of the physiological cell death process, including loss of adhesion and nuclear envelope breakdown (lamin phosphorylation and solubilization), were not altered in this clone. The absence of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
122
0
1

Year Published

1995
1995
2000
2000

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(130 citation statements)
references
References 53 publications
7
122
0
1
Order By: Relevance
“…Both hyperthermia and ATP depletion were found to induce protein aggregation, and suppression of the aggregation in stressed cells with the elevated HSP content [9,16] may be responsible for the protection from these apoptosis-inducing exposures. Suggested suppression of actin aggregation by HSPs [21] is of special importance since G-actin (but not F-actin) is a potent inhibitor of DNase I which can be involved in apoptotic DNA fragmentation [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Both hyperthermia and ATP depletion were found to induce protein aggregation, and suppression of the aggregation in stressed cells with the elevated HSP content [9,16] may be responsible for the protection from these apoptosis-inducing exposures. Suggested suppression of actin aggregation by HSPs [21] is of special importance since G-actin (but not F-actin) is a potent inhibitor of DNase I which can be involved in apoptotic DNA fragmentation [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about the endonuclease(s) responsible for ladder production besides its dependence on pH and the presence of Ca 2+ or Mg 2+ ions in mammals (Cohen and Duke, 1984;Arends et al, 1990). Several candidate nucleases have been proposed, including DNase I (Ucker et al, 1992;Peitsch et al, 1993), DNase II (Barry and Eastman, 1993) and Nuc 18 (Caron-Leslie et al, 1991); hence, identifying enzymes which produce DNA fragments with blunt, 5' phosphorylated ends may help to discern the nucleases that have a physiological role. We note that the only endonuclease activity shown to generate these types of DNA ends in vivo is the V(D)J recombinase encoded in part by RAG-1 and RAG-2 (Schlissel et al, 1993) which could conceivably participate in ladder production in the thymus, and perhaps the CNS where RAG-1 is expressed (Chun et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…However, the percentage of TUNEL-positive cells generated in the presence of the drug combination was approximately half the percentage of cells showing nuclear condensation under the same conditions. Others have also observed that DNA degradation is not always detected in cells undergoing apoptosis as de®ned by morphological criteria (Tomei et al, 1993;Ucker et al, 1992).…”
Section: Synergistic Induction Of Apoptosis By Hma and Etoposide Treamentioning
confidence: 99%